Restating research findings in research articles discussion section : a corpus analysis of linguistic cues and lexical bundles - Jasim, Yasir Bdaiwi (Penerbit Universiti Kebangsaan Malaysia, 2023)
The discussion section is considered one of the most crucial sections of a research article (RA). It is challenging and problematic for both novice and native writers due to its argumentative nature. This section serves various functions such as restating results, interpreting the results, comparing them with the literature, and presenting claims and contributions. However, the focus of this paper is on a particular move function which is Restating Research Findings. Although this communicative move has been found to be obligatory or conventional in recent studies that investigated different disciplines, the present paper is only concerned with medical science discipline. Every communicative move serves a certain function that may be initiated by formulaic expressions, known as ‘lexical bundles’ (LBs) which are realised by the use of certain linguistic devices. This study explores these linguistic devices and the lexical bundles associated with move Restating Research Findings in the discussion section of medical research articles (MRAs). The analysed corpus is 50 discussions of research articles published in high impact journals. The findings showed that this move appeared in all the selected discussions. The move of Restating Research Findings was realised by the employment of reporting verbs (e.g., find, show) and first person plural pronouns (we, our). Also, the move was initiated by a number of 3-word and 4-word LBs such as Our study shows that and Our results revealed that. These findings could guide research writers in the field of medicine to produce a clearly presented discussion section.